A Solution for Automated Grading of QDA Homework - Kaufmann, Andreas; Riehle, Dirk; Krause, Julia; Harutyunyan, Nikolay (HICSS Proceedings, 2023)
Teaching research methods is important in any curriculum that prepares students for an academic career. While theoretical frameworks for qualitative theory building can be adequately conveyed through lecturing, the practices of qualitative data analysis (QDA) cannot. However, using experiential learning techniques for teaching QDA methods to large numbers of students presents a challenge to the instructor due to the effort required for the grading of homework. Any homework involving the coding of qualitative data will result in a myriad of different interpretations of the same data with varying quality. Grading such assignments requires significant effort. We approached this problem by using methods of inter-rater agreement and a model solution as a proxy for the quality of the submission. The automated agreement data serves as the foundation for a semi-automated grading process. Within this paper, we demonstrate that this proxy has a high correlation with the manual grading of submission
Keywords: Advances in Teaching and Learning Technologies; homework evaluation; inter-rater agreement; qualitative data analysis

A systematic literature review of pre-requirements specification traceability - Mucha, Julia; Kaufmann, Andreas; Riehle, Dirk (Requirements Engineering, 2024)
Requirements traceability (RT) is the ability to link requirements to other software development artifacts. In pre-requirements (pre-RS) traceability, requirements are linked to their origin, such as interviews with stakeholders, meeting protocols, or legacy systems. Compared with post-RS traceability, which links requirements to source code and other later artifacts, pre-RS traceability has seen much less research. This article presents a systematic literature review of pre-RS traceability based on 77 articles published between 1992 and 2022, aiming to provide a comprehensive overview of its use cases, benefits, problems, and solutions. Through the analysis of existing literature, this review identifies gaps for future research and establishes a foundation for future investigations in the field of pre-RS traceability.<br
Keywords: Pre-requirements specification traceability; Requirements traceability; Requirements engineering; Systematic literature review

A validation of QDAcity-RE for domain modeling using qualitative data analysis - Kaufmann, Andreas; Krause, Julia; Harutyunyan, Nikolay; Barcomb, Ann; Riehle, Dirk (Requirements Engineering, 2022)
Using qualitative data analysis (QDA) to perform domain analysis and modeling has shown great promise. Yet, the evaluation of such approaches has been limited to single-case case studies. While these exploratory cases are valuable for an initial assessment, the evaluation of the efficacy of QDA to solve the suggested problems is restricted by the common single-case case study research design. Using our own method, called QDAcity-RE, as the example, we present an in-depth empirical evaluation of employing qualitative data analysis for domain modeling using a controlled experiment design. Our controlled experiment shows that the QDA-based method leads to a deeper and richer set of domain concepts discovered from the data, while also being more time efficient than the control group using a comparable non-QDA-based method with the same level of traceability.
Keywords: Domain model; Domain modeling; Qualitative data analysis; Requirements engineering; Controlled experiment

Generating Image Descriptions for SmartArts - Voegler, Jens; Krause, Julia; Weber, Gerhard (Computers Helping People with Special Needs, 2016)
Visual information such as SmartArts are often used in presentations and lectures. SmartArts are visual information containing some text and graphical elements. They have to be described verbally to become accessible for visually impaired and blind people. But a manual image description is often not provided or misses information about the pictorial part of SmartArt diagrams. We present a PowerPoint Add-In to create image descriptions semiautomatically. Both a short description and a long description containing details are generated. The author can adjust the generation by modifying a template. In a user evaluation the quality of manually and semi-automatic transcribed images were tested.<br
Keywords: SmartArt; Alternative description; Images

The Benefits of Pre-Requirements Specification Traceability - Krause, Julia; Kaufmann, Andreas; Riehle, Dirk; Jung, Martin (Proceedings of the 30th International IEEE Requirements Engineering Conference (RE 2022), 2022)
Requirements traceability is the ability to trace requirements to other software engineering artifacts. Traceability can be classified as either pre- or post-requirements specifications (RS) traceability. Pre-RS traceability is the ability to trace between requirements and their origin. However, the benefits of pre-RS traceability are often not clear. In this article, we systematically lay out the benefits of pre-RS traceability. We present results from both a literature review and a qualitative survey of practitioners involved with documenting and utilizing such trace links. We find that the benefits strongly depend on the practitioners, their tasks, and the project environment. Awareness of these relationships supports a clearer understanding of the benefits of pre-RS traceability and thus motivates successful implementation of the required practices. The results of our research motivates the adoption of pre-RS traceability and present problem areas for future research.<br
Keywords: Requirements Engineering; Requirements Traceability; Pre-Requirements specification Traceability; Literature review; Qualitative Survey

The Code System of a Systematic Literature Review on Pre-Requirements Specification Traceability - Krause, Julia; Kaufmann, Andreas; Riehle, Dirk (2020)
Tracing requirements back to their origin is important to understand the context and to identify all potential concerns or conflicts in the genesis of the requirements. The so-called pre-requirements specification (pre-RS) traceability is part of requirements traceability (RT) and is recognized as an important factor for long-term project success. Different approaches have been developed to connect requirements and their origin, but still, there is no general established solution. Mostly it is seen as an effort without significant benefits leading to resistance towards its implementation. To guide future research, a comprehensive understanding of the use cases, benefits, challenges, and existing approaches encountered is vital. However, the landscape of the scientific literature on this field remains somewhat fragmented, with pre-RS traceability often only considered in the periphery. We, therefore, conducted a systematic literature review, which identified 67 relevant papers. The literature was coded using qualitative data analysis (QDA) methods. In this technical report, we present the whole resulting code system of the QDA and describe the relationships between the identified themes, focusing on the relevance, problems, solutions, and techniques of pre-RS traceability.<br
Keywords: Pre-Requirements Specification Traceability; Requirements Traceability; Requirements Engineering; Qualitative Data Analysis

The QDAcity-RE-RS Method for Creating Complete, Consistent, and Traceable Requirements Specifications - Mucha, Julia (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2023)
Resolving issues that arise in a software project becomes more expensive as the project advances. Hence, it is crucial for a requirements engineer to develop a complete, consistent, and traceable requirements specification (RS). To create such a high-quality RS, the requirements engineer must develop a deep understanding of the problem domain. In science, researchers face a similar challenge when building theories. Constructing a theory requires considering all related resources to capture a broad diversity of characteristics. In addition, researchers must document the theory-building process to demonstrate high quality and ensure traceability for other researchers who want to build on the theory. Therefore, researchers developed methods for theory building, from which we draw inspiration for our research. In this dissertation, we present the development and evaluation of the tool-supported QDAcity-RE-RS method, which utilizes qualitative data analysis (QDA). Thus this method supports the analysis of stakeholder information, such as interview transcripts to create natural language RS. We followed the design science process proposed by Peffers et al. (2007), which focuses on developing and evaluating an innovative artifact to solve a clearly defined problem. To identify the problem, we performed a systematic literature review (SLR) and conducted an exploratory qualitative survey with 14 RE experts from the industry. Based on the findings, we developed the QDAcity-RE-RS method and implemented its tool-support. To demonstrate the method, we conducted a case study and triangulated it using a focus group session with 38 RE experts from the industry. Subsequently, we evaluated the artifact by using two approaches. Firstly, we evaluated the tool-support using a heuristic evaluation, which uncovered five usability issues and nine additional improvements. Secondly, we evaluated the QDAcity-RE-RS method by performing an evaluatory case study in an industry project. This study reveals that the method supports various activities within the RE process, such as documenting decisions and preparing stakeholder meetings. The RS resulting from the QDAcity-RE-RS method was complete concerning the analyzed stakeholder information but lacked requirements on topics that were not explicitly discussed, such as requirements for the backend. Notably, the RS demonstrated a strong suit in maintaining consistent usage of technical terms, whereas the requirements in the industry project exhibited numerous variations of technical terminology. The pre-RS traceability of the requirements to their origin and thus to decisions was found to be very helpful by the requirements engineer of the industry project, as it facilitates the transfer of information to other requirements engineers. The resulting tool-supported QDAcity-RE-RS method facilitates the creation of a natural language RS, enables the documentation of the creation process, and thereby realizes pre-RS traceability. By linking requirements to their origin, the method allows for assessing completeness and identifying inconsistencie
Keywords: Requirements Engineering; Traceability; Requirements Specification; Method; QDAcity